2002
DOI: 10.3354/ame029199
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of primary production and community respiration in the ocean: implications for regional carbon studies

Abstract: Primary production (P) and community respiration (R) were measured in vitro along 2 transects of a trans-oceanic section crossing the oligotrophic North Atlantic waters, and during a drifter experiment in the eutrophic waters of the Northwest Africa upwelling system. Our results indicate that the scales of variability of P and R are different, R being less variable than P in the 2 studies. In the first transect of the oceanic study, the mean P:R ratio was <1 (0.8), while in the second transect it was >1 (1.1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
40
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 54 publications
14
40
4
Order By: Relevance
“…As previously reported , Arístegui & Harrison 2002, variability in integrated GPP was much higher than in CR (6-versus 2-fold). Given that bacterial biomass was clearly less than that of autotrophs in the photic layer, a balanced or even net autotrophic balance would have been expected according to trophic distribution models (Gasol et al 1997).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As previously reported , Arístegui & Harrison 2002, variability in integrated GPP was much higher than in CR (6-versus 2-fold). Given that bacterial biomass was clearly less than that of autotrophs in the photic layer, a balanced or even net autotrophic balance would have been expected according to trophic distribution models (Gasol et al 1997).…”
Section: Discussionsupporting
confidence: 60%
“…Resale or republication not permitted without written consent of the publisher (Fernández & Pingree 1996, Arístegui & Harrison 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Similar threshold values of GPP have been reported for other coastal upwelling systems (Duarte et al 2001) and other coastal areas around the world (Duarte et al 2004, Duarte & Regaudie-deGioux 2009) in general, but it is considerably higher than the values reported for the oligotrophic ocean (Arístegui & Harrison 2002, McAndrew et al 2008, Duarte & Regaudie-de-Gioux 2009.…”
Section: Discussionmentioning
confidence: 57%
“…Considering the whole sampling period, the model outcome indicates that the metabolic balance of nano-and microplankton exhibited higher variability than the metabolic balance of picoplankton. This circumstance leads us to conclude that fluctuations in autotrophic biomass, mainly diatoms and nanoflagellates, and the consequent changes in primary production control the transition from net heterotrophy to net autotrophy (Duarte et al 2001, Arístegui & Harrison 2002, McAndrew et al 2007, Arbones et al 2008 in the NW Iberian upwelling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have endeavored to define oceanic biomes based on microbial data (e.g., Zwirglmaier et al, 2008;Zinger et al, 2011;Gibbons et al, 2013), while other studies have shown that fronts can enhance microbial activity (e.g., Arístegui and Harrison, 2002) or delimit the distribution of the bacterioplankton community composition in surface waters (Baltar et al, 2016). However, there is almost no information on how surface frontal systems influence the distribution of microbial community composition and activity in the dark water column, which contains around 75% of the prokaryotic biomass and 50% of the prokaryotic production of the global ocean ).…”
Section: Introductionmentioning
confidence: 99%